(untitled) (TUTA Journal, 2022)
Going abroad has become the dream of Nepali youths and it has spread rapidly in the country. This dream’s root is the Gurkha soldiers’ recruitment in the past as it has developed the thought of being lahure and going across the border for employment. Akhand Bhandari’s Malaya Express raises the issue of youths’ transnational migration for employment. This article inquires causes of Nepali youths’ choice for foreign employment, its impact and the actions to be taken to change the trend of it. The theoretical tools of transnationalism developed by Vertovec, Levitt and Jaworsky, and Faist and Fauser are taken for the research purpose. The major objectives of the study are to point out the major reasons of transnational migration of Nepali youths, to identify the impacts and to analyze the ways to keep them in the country. The study finds out some positive and negative impacts of transnational migration. The study finds out that unemployment, peer pressure and the trend of migrating for employment are some causes of Nepali youths’ choice for transnational migration. Though transnational migration benefits remittances, it invites many problems in migrants’ lives and transnational families. It focuses on some solutions of transnational migration. The major conclusion of the study is that Nepali youths migrate to Gulf countries for employment and develop the web of relationship. They have emotional and social problems in host land, but they are bound to struggle for their future. They do not live there forever; they return to the homeland after visa time. Opportunities for employment and security of future will help Nepali youths to decide to stay in Nepal.